A New Species of Rana from the Terai of Nepal - Das, Indraneil (Society for the Study of Amphibians and Reptiles, 1998)
new species of Rana is described from the terai region of Nepal on the basis of three specimens. The new species is diagnosable from known congeners in possessing the following characteristics: head longer than wide; tympanum rounded, smaller than orbit diameter; supratympanic fold absent; finger I longer than finger II; a series of large, flat glands on lateral aspect of body; broad webbing on toe IV to penultimate subarticular tubercle, reaching tip of toes as a narrow sheath; tips of digits flattened to form disks with distinct circummarginal grooves separating dorsum of disks from ventrum; tibia length/snout-vent length ratio 47.23-54.15; and absence of humeral gland on forelimb of males. The snout-vent length range shown by the type series is 30.4-32.5 mm.